Chinese digestive surgery interns’ learning quality and English reading proficiency during COVID-19 pandemic: Comparison between face-to-face versus WeChat teaching and learning - Wei Zhou; Zehua Wang; Feifei Han; Liu Hong (Heliyon, 2023)
Gastrointestinal clinical teaching is of vital important for gastrointestinal surgery interns. However, during COVID-19 pandemic, due to frequent lockdowns and essential social distancing policy implemented in China, face-to-face teaching was interrupted significantly. To find a cost-effective way to deliver medical education to ensure that teaching and learning would be continued and uninterrupted, many social media tools and mobile applications have been used in medical teaching and learning. WeChat has been frequently employed in teaching and learning in many disciplines in Chinese universities due to its powerful functions and free cost. This study compared Chinese digestive surgery interns' learning quality, English reading proficiency, and learning satisfaction in two teaching conditions: the traditional face-to-face teaching versus WeChat teaching via an experiment. The study recruited 60 final year clinical medical students, who were randomly and equally assigned into two groups: traditional face-to-face teaching versus WeChat teaching. Interns' learning quality and learning satisfaction were measured by Likert-scale questionnaires; and their English reading proficiency was measured by the reading section in a standardized English test. The results showed that interns in WeChat group had significantly higher learning quality on understanding mechanisms and current knowledge by both self-assessment and peer-assessment. WeChat group also outperformed face-to-face group on inferencing, details, and main ideas in English reading. With regard to learning satisfaction, WeChat group were higher on learning interests, learning objectives, learning format, and English reading proficiency than face-to-face group. However, interns did not differ in terms of their learning satisfaction on medical skills, which might indicate that WeChat had limitations on training interns’ medical practical ability.